Myocardial fibrosis and its relation to adverse outcome in transposition of the great arteries with a systemic right ventricle. (15th November 2018) - Broberg, Craig S.; Valente, Anne Marie; Huang, Jennifer; Burchill, Luke J.; Holt, Jonathan; Van Woerkom, Ryan; Powell, Andrew J.; Pantely, George A.; Jerosch-Herold, Michael
Abstract: Background: Myocardial dysfunction has been implicated in gradual heart failure in transposition of the great arteries (TGA) with a systemic right ventricle (RV). Fibrosis can be assessed using the extracellular volume fraction (ECV). Our aim was to measure ECV and determine its associations with clinical findings and outcomes. Methods: We prospectively measured ECV in systemic RV subjects (either D-loop after atrial switch or L-loop) and healthy controls. T1 measurements for a single mid-ventricular short-axis plane before and 3, 7, and 15 min after gadolinium contrast were used to quantify systemic ventricular ECV. Individuals with elevated ECV were compared to those without. Results: In 53 TGA subjects (age 34.6 ± 10.3 years, 41% female) the mean ECV for the systemic RV (28.7 ± 4.4%) was significantly higher than the left ventricle in 22 controls (26.1 ± 2.8%, P  = 0.0104). Those with an elevated ECV ( n  = 15, 28.3%) had a higher b-type natriuretic peptide (BNP) ( P  < 0.011) and a longer 6-min walk distance ( P  = 0.021), but did not differ by age, arrhythmia history, ventricular volume, function, or circulating collagen byproducts. At follow-up (median 4.4 years), those experiencing major cardiovascular endpoints (new arrhythmia, arrhythmia device, heart failure hospitalization, listing for transplantation, mechanical support, or cardiovascular death, n  = 14) had a higher ECV. ECV, age, and BNP were independent predictors of cardiac events in Cox-proportional hazard models. Conclusions: Myocardial fibrosis is common in the systemic RV and associated with a higher BNP. Elevated CMR-derived ECV was associated with adverse clinical outcome. The findings suggest a role of diffuse myocardial fibrosis in clinical deterioration of the systemic RV. Highlights: Patients with a systemic right ventricle show CMR evidence of diffuse myocardial fibrosis. Fibrosis as shown by CMR is not associated with other findings associated with myocardial dysfunction. Systemic RV patients with CMR evidence of fibrosis have more cardiovascular events in 4 years.